Faktor-faktor yang Berkontribusi terhadap Multiple Inteligences Siswa Kelas X SMK PGRI Kandanghaur Kabupaten Indramayu - Sahrudin Sahrudin (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2022)
In the process of learning, multiple intelligences is necessary, because someone who does not have multiple intelligences in learning will not be possible to respond quickly and what was delivered was a teacher in the learning process in the classroom and outside the classroom. Factor that contribute to students' multiple intelligences including the culture of the school, the family, education and peer interaction. The school culture of discipline in carrying out the order, and school programs will increase the multiple intelligences of students. In addition, the pattern of family education and social peers contribute to the emergence of multiple intelligences of students.